Lead and Zinc contamination of surface sediments in the main harbours of the Galician Rias - Prego, R.; Ferro, P.; Trujillo, C. (Journal of Iberian Geology, 2008)
The concentration ranges and degree of contamination of lead and zinc in the four principal harbour areas of the northwest Iberian Peninsula have been defined from 130 surface sediment samples (